2017
DOI: 10.1002/jcp.25733
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MSX1 and DCLK1 as mRNA Biomarkers for Colorectal Cancer Detection Through DNA Methylation Information

Abstract: Colorectal cancer is the second most deadly malignancy in the United States. However, the currently screening options had their limitation. Novel biomarkers for colorectal cancer detections are necessary to reduce the mortality. The clinical information, mRNA expression levels and DNA methylation information of colorectal cancer were downloaded from TCGA. The patients were separated into training group and testing group based on their platforms for DNA methylation. Beta values of DNA methylation from tumor tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…With the development of high-throughput sequencing, microarray technology and bioinformatics, more and more biomarkers have been discovered to effectively predict the prognosis of patients with CRC [17]. For example, Ai-Jun Sun et al started bioinformatics data mining from the DNA methylation information in the tcga database and found that MSX1 and DCLK1, which are involved in DNA methylation, may be used as biomarkers for CRC [18]. Zong Z et al found that MSI-2 is highly expressed in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing, microarray technology and bioinformatics, more and more biomarkers have been discovered to effectively predict the prognosis of patients with CRC [17]. For example, Ai-Jun Sun et al started bioinformatics data mining from the DNA methylation information in the tcga database and found that MSX1 and DCLK1, which are involved in DNA methylation, may be used as biomarkers for CRC [18]. Zong Z et al found that MSI-2 is highly expressed in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that combination of DCLK1 inhibition with irradiation has a synergistic effect in HNSCC cell lines [ 11 ]. DCLK1 is therefore considered as an attractive and potential therapeutic target in the treatment of malignant tumors [ 30 , 31 ]. Due to the limitations of currently available evidence on the therapeutic effects and molecular biology of DCLK1 in malignant tumors, Further studies are warranted to investigate these in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…These results would be valuable for functional genomic studies of desert plants under abiotic stresses (Long et al 2014). In another RNAseq study in H. ammodendron, RNA-seq analyses have identified a total of 87,109 unigenes and 3353 of them were differentially expressed in shoots and 4564 of them differentially expressed in in roots (Gao et al 2017).…”
Section: Haloxylon Ammodendronmentioning
confidence: 95%
“…Novel biomarkers are important for detection of growth, development, and disease resistance. Single cell RNA-seq is valuable to elucidate cell type composition through identification of transcripts and biomarkers; for example, methylated genomic locations could be used to build the model for disease detection (Sun et al 2017). RNA nextgeneration sequencing could be used to characterize patterns of miRNAs and comprehensive profiling of miRNA transcriptome will provide to be useful for further functional validation and biomarker identification (Gecaj et al 2017).…”
Section: Single-cell Rna-sequencing For Elucidating Cell Type Composimentioning
confidence: 99%